2021
DOI: 10.1111/1365-2435.13989
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effects of climate warming and nitrogen deposition vary with home and introduced ranges

Abstract: Maternal effects, which can be defined as the contribution of a maternal individual to the phenotype of its offspring beyond the equal chromosomal contribution, were identified as long ago as 1909 (Roach & Wulff, 1987). Since then, related studies have gained con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The maternal effects on the growth strategy of clonal offspring Maternal effects have become an important field of study in ecology, and there is an ongoing debate regarding their adaptive significance for offspring fitness (Marshall and Uller, 2007). Maternal effects can be either adaptive if they increase offspring fitness or not if they are neutral or harmful to the fitness of offspring (Galloway and Etterson, 2007;Donelson et al, 2018;Zhou et al, 2021). In this study, the clonal offspring of different UV-B radiated parents displayed various performances, despite they were in an unirradiated environment (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maternal effects on the growth strategy of clonal offspring Maternal effects have become an important field of study in ecology, and there is an ongoing debate regarding their adaptive significance for offspring fitness (Marshall and Uller, 2007). Maternal effects can be either adaptive if they increase offspring fitness or not if they are neutral or harmful to the fitness of offspring (Galloway and Etterson, 2007;Donelson et al, 2018;Zhou et al, 2021). In this study, the clonal offspring of different UV-B radiated parents displayed various performances, despite they were in an unirradiated environment (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal effects occur when the environment experienced by the mother influences the offspring phenotype over and above the direct effect of transmitted genes ( Marshall and Uller, 2007 ). Despite the importance of maternal effects has been confirmed by many studies ( Galloway and Etterson, 2007 ; Marshall and Uller, 2007 ; Auge et al, 2017b ; Lyu et al, 2017 ; Donelson et al, 2018 ; Zettlemoyer and Lau, 2021 ; Zhou et al, 2021 ), the adaptive significance of maternal effects is often controversial. Some studies have found that adaptive maternal effects are widespread, allowing offspring to cope with rapidly changing environments or even increase fitness ( Yin et al, 2019 ; Donelan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the adaptive response of organisms to changing environmental conditions is a major theme in ecology and evolutionary studies. A key component of this adaptability is phenotypic plasticity, which refers to the potential of an organism to change its phenotype in response to different environments, independent of their genotype (Donelan et al., 2020; O'Dea et al., 2016; West‐Eberhard, 2003; Zhou et al., 2022). By expressing plastic phenotypes, populations may experience lower demographic costs (Donelan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By expressing plastic phenotypes, populations may experience lower demographic costs (Donelan et al., 2020). Albeit not genetically fixed, plastic changes of the phenotype can sometimes be transmitted to the next or multiple generation (inter‐ or transgenerational plasticity, ITGP) via the environment experienced by a parent influencing the development of their offspring (Latzel et al., 2023; Marshall & Uller, 2007; Puy et al., 2021; Wang et al., 2022; Zhou et al., 2022). Parents can change offspring phenotypes without affecting nucleotide sequence by multiple non‐genetic processes such as parental effects, for example, nutrient, hormone and protein transmission (Lacey, 1996; Zahra et al., 2021), or by epigenetic inheritance such as noncoding small RNAs, DNA methylation and histone modification (Danchin et al., 2011; Kong et al., 2020; Maury et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation